Estudio de los musgos terrestres (bryophyta) presentes en el sendero quishuar del área recreacional el boliche, parque nacional Cotopaxi, Ecuador. - Catota Toapanta, Jessica Adriana (2020)
This project was carried out with the aim of making a bryological inventory of the Quishuar trail in the recreational area of Boliche, Cotopaxi National Park, Cotopaxi Province, Ecuador. Additionally, the information was collected regarding the current state of knowledge of the muscovado flora of Cotopaxi Province. Two fundamental sources of information on mosses in Ecuador were reviewed, www.tropicos.org and the Herbarium of the Pontifical Catholic University of Ecuador (QCA). A total of 233 samples were reviewed from the Cotopaxi province; this Cotopaxi muscovado flora is taxonomically divided into 36 family, 114 genus and 212 species. From this analysis we conclude that the dominant families are Pottiaceae con: (22 genera / 39 species), Bryaceae (12 genera / 23 species) and Bartramiaceae (8 genera / 18 species). With respect to the inventory of terrestrial mosses in the study area, a total of 44 specimens were collected, distributed in 12 families and 18 genera. The reported taxa are: Andreaea (Andreaeaceae), Aerolindigia, Brachythecium (Brachytheciaceae), Acidodontium, Bryum, Rhodobryum (Bryaceae), Calymperes, (Calymperaceae), Compylopus, Dicranella, (Dicranaceae), Hypnum (Hypnaceae), Neckera, Porotrichum, Thamnobryum (Neckeraceae): Callicostella (Pilotrichaceae): Didymodon (Pottiaceae), Pogonatum (Polytrichaceae): Sematophyllum (Sematophyllaceae), Thuidium (Thuidiaceae) In conclusion, we can indicate that the flora of the province is scarcely inventoried, being Latacunga canton the region with more reports of the brioflora, this work represents the first report of the terrestrial mosses of this recreational area. More similar studies are recommended for the province and the UTCEC herbarium with important methodologies for the knowledge of students and communities within the province of Cotopaxi Ecuador.